Influence of mover yoke and winding connections on unbalanced normal force for double‐sided linear switched reluctance machine. Issue 2 (1st February 2016) - Wang, Qianlong; Chen, Hao; Xu, Tong; Yuan, Jinxia; Wang, Jiewei; Abbas, Saleem
Abstract : Due to the manufacturing inaccuracies or wear, the mover eccentricity of the double‐sided linear switched reluctance machine (DLSRM) is practically inevitable, which gives rise to undesirable unbalanced normal force (UNF). This study investigates the UNF reduction methods in the eccentric DLSRM. According to the finite element analysis and magnetic circuit analysis, the flux distributions and the UNF of the healthy and eccentric DLSRM are compared, and it is proved that removing the mover yoke can alleviate the UNF in the eccentric situation. Furthermore, the effects of the stator winding connections on UNF are analysed via a transient two‐dimensional finite element model. It shows that the UNF can also be reduced by connecting the coils of the windings in parallel. For verifying the two proposed methods, a prototype experimental platform is established, and the experimental results validate the analyses.